Nurcholish Madjid and beyond: an analysis of the contemporary discourse on religious pluralism in Indonesia - Maulana, Arif; Moris, Megawati (IIUM Press, International Islamic University Malaysia, 2017)
This study investigates the continuation of the discourse on religious pluralism and Nurcholish’s influence on its development after his death. This research seeks to explicate Nurcholish’s views and arguments on religious pluralism and to examine the developments of contemporary discourse on religious pluralism in Indonesia after him. It attempts to show his contribution to the successive discourse of the proponents of religious pluralism. Another primary focus of this research is to evaluate the main arguments presented by the opponents of religious pluralism in Indonesia, led by MUI and followed by Muslim intellectuals with special reference to the doctrines of the ultimate Reality, absolute truth claims, chosenness and salvation. The findings of this study indicate that religious pluralism discourse in Indonesia is still rampant and has great influence on Indonesian society—with negative implications—despite facing great opposition from mainstream Muslims. Although, this humble research has limitations in term of its scope, hopefully it would be able to contribute to the body of knowledge on religious pluralism and provoke further discussion on it.